Complete chloroplast genome sequence of Chrysosplenium macrophyllum and Chrysosplenium flagelliferum (Saxifragaceae). Issue 3 (2nd July 2020) - Yan, Wen-Jie; Yang, Tian-Ge; Liao, Rui; Wu, Zhi-Hua; Qin, Rui; Liu, Hong
Abstract: The complete chloroplast genome of Chrysosplenium macrophyllum Oliv. and Chrysosplenium flagelliferum Fr. Schmidt. were reported in this study. The chloroplast genomes were 152, 837 bp for C. macrophyllum and 151, 679 bp for C. flagelliferum . LSC and SSC of 83, 584 bp and 17, 265 bp were separated by two IRs of 25, 994 bp each in C. macrophyllum . While C. flagelliferum contained IRs of 25, 973 bp, LSC of 82, 772 bp and SSC of 16, 961 bp, for a total 151, 679 bp length. The chloroplast genome of Chrysosplenium macrophyllum contains 130 genes, including 85 protein-coding genes (78 PCG species), 8 ribosomal RNA genes (4 rRNA species), 37 transfer RNA genes (30 tRNA species). And the chloroplast genome of Chrysosplenium flagelliferum contains 130 genes, including 85 protein-coding genes (78 PCG species), 8 ribosomal RNA genes (4 rRNA species), 37 transfer RNA genes (30 tRNA species).